Delayed Valuation: A Reanalysis of Goal Features, "Upward" Complementizer Agreement, and the Mechanics of Case. (12th December 2015) - Carstens, Vicki
Abstract: There are at least four opposing views on the directionality and configuration of Agree relations. In mainstream minimalism, Agree is strictly downward "probing" (Chomsky2000, 2001 ; Bošković2007 ; Epstein & Seely2006 ), but some recent works argue that Agree always looks upward (Zeijlstra2012, Wurmbrand2012 ). A third perspective takes agreement to follow from the Spec–head configuration (Koopman2006 ), and under a fourth proposal, the directionality of Agree varies parametrically (Baker2008 ). Although each approach has some empirical support, none achieves the strict conceptual necessity that is a central goal of minimalist theory. I argue, following Epstein's (1999 ) approach to c‐command, that a downward directionality for Agree follows automatically and necessarily from the bottom‐to‐top construction of syntactic objects. But if a uF does not find any source of valuation in its c‐command domain at first Merge, directionality‐free matching and delayed valuation are possible up to the point of cyclic Transfer. The approach eliminates several stipulations from agreement theory, deducing that the uFs making goals "active" in Agree relations are simply those that find no match in their c‐command domains at Merge.